2019
DOI: 10.21608/jpp.2019.68550
|View full text |Cite
|
Sign up to set email alerts
|

Response of some Bread Wheat Genotypes to Less Irrigation Water

Abstract: This study was performed at Sakha Agricultural Research Station, Kafer El-Sheikh, Egypt, in 2014/2015 and 2015/2016 seasons under normal (five irrigation) and reduced irrigation (only one irrigation after planting one) regimes. Eighteen bread wheat genotypes were used to study the agronomic and morphophysiological characters and tolerance indices to distinguish wheat high yielding genotypes under reduced irrigation. The used genotypes were evaluated using randomized complete block design. The results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The variation among wheat genotypes in number of spikes/m 2 could be attributing to genetic variation (Table 2). These results are in harmony with those reported by Salem, (2005) found significant differences among eight bread wheat varieties in number of spikes/m 2 , Khalil et al, (2006), Gab Alla (2007, Abd El-Rahman (2008) and Abdel-Nour and Fatheh (2011) confirmed similar obtained results. Data presented in Table (4) indicated that, the genotype; Gemmeiza 11 recorded the highest values for number of grains/spike, biological yield, and straw yield.…”
Section: -Mean Performancesupporting
confidence: 92%
“…The variation among wheat genotypes in number of spikes/m 2 could be attributing to genetic variation (Table 2). These results are in harmony with those reported by Salem, (2005) found significant differences among eight bread wheat varieties in number of spikes/m 2 , Khalil et al, (2006), Gab Alla (2007, Abd El-Rahman (2008) and Abdel-Nour and Fatheh (2011) confirmed similar obtained results. Data presented in Table (4) indicated that, the genotype; Gemmeiza 11 recorded the highest values for number of grains/spike, biological yield, and straw yield.…”
Section: -Mean Performancesupporting
confidence: 92%
“…In this context, there are many stress tolerance indices were developed such as mean productivity, (Rosielle and Hamblin, 1981), geometric mean productivity, stress tolerance index (Fernandez, 1992), and harmonic mean (Jafari et al, 2009) that were used in the current investigation. Singh et al (2015, a and b), Ali and El-Sadek (2016), Darwish et al (2017) andGab Alla et al (2019) on bread wheat, and Mohammadi (2016) on durum wheat, reported highly significant associations among some stress tolerance indices indicating that these indices are similar for ranking stress tolerant genotypes which allows to use only one of them.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the Egyptian government has established giant agricultural projects to cultivate vast areas in the Western Desert. To achieve this goal, wheat researchers made an exceptional effort to carry out a large number of field experiments for evaluating wheat genotypes under environments suffering from abiotic stresses (El Ameen, 2012; Darwish et al, 2017;Gadallah et al, 2017;Noreldin and Mahmoud, 2017;Gab Alla et al, 2019;Hagras and Moustafa, 2019;Mohiy et al, 2021;Darwish et al, 2022;Ibrahim and Said, 2020;Sayed et al, 2022 andElfanah et al, 2023). These researches have resulted in the development of wheat varieties that can be grown in unfavorable environments as well as in the new reclaimed lands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation